2009
DOI: 10.1038/clpt.2008.294
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes Associated With Reduced Activity of VKORC1 and CYP2C9 and Their Modification of Acenocoumarol Anticoagulation During the Initial Treatment Period

Abstract: The objective of this study was to investigate the influence of genotypes associated with reduced activity of vitamin K epoxide reductase complex subunit 1 (VKORC1) and cytochrome P450 2C9 (CYP2C9) on anticoagulation with acenocoumarol during the first 6 weeks of treatment. In 1,525 patients from the Rotterdam Study who were started on anticoagulation therapy with acenocoumarol, the presence of VKORC1 1173C>T and CYP2C9*2 and *3 allele variants was determined. The first international normalized ratio (INR) aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…The frequencies of selected SNPs correlate with other European populations (7,22,33,35,36,38,42) and thus with Caucasians (17). This type of study was done for the fi rst time in Slovakia.…”
Section: Discussionmentioning
confidence: 99%
“…The frequencies of selected SNPs correlate with other European populations (7,22,33,35,36,38,42) and thus with Caucasians (17). This type of study was done for the fi rst time in Slovakia.…”
Section: Discussionmentioning
confidence: 99%
“…CYP4F2 was shown to catalyze vitamin K oxidation, while the presence of 433Met variation reduced its catalytic ability, potentially leading to accumulation of the VKORC1 substrate -vitamin K epoxide and larger warfarin doses required for inhibition of this pathway (McDonald et al, 2009). CYP4F2 Val433Met was also associated with acenocoumarol dose requirements with similar modest effect (1.2-1.3%) (Perez-Andreu et al, 2009;Teichert et al, 2009).…”
Section: Fig 1 Targets Of Anticoagulants and Direct Thrombin Inhibimentioning
confidence: 83%
“…The investigators found that carriers of *2,*3 required more time to achieve stable dosing (hazard ratio HR=0. (Stehle et al, 2008;Teichert et al, 2009). Thus, significant contribution of common hypofunctional CYP2C9 variants to warfarin sensitivity has been well-established, although accurate estimates of their contribution varies between studies and is dependent on inclusion of other factors.…”
Section: Fig 1 Targets Of Anticoagulants and Direct Thrombin Inhibimentioning
confidence: 99%
“…Although the FDA updated the warfarin label already in 2008 (Teichert et al, 2009a;Food and Drug Administration [FDA], 2007), genotyping preceding the anticoagulation therapy with coumarin derivatives is not commonly performed. Currently, health care professionals' attitudes are reserved towards pharmacogenetic dosing.…”
Section: Health Care Professionalsmentioning
confidence: 99%